Characterization of enamel after the use of oral hygiene auxiliaries with whiteners = Caracterización del esmalte después del uso de auxiliares de higiene bucal con blanqueadores - Zavala Alonso, Norma Verónica
The purpose of this study was to evaluate the effect of the use of the combined auxiliaries of oral hygiene with whitening agents on the micro-hardness and micro-morphology of dental enamel. Materials and Methods. 40 human incisors were used and sectioned to obtain 4x4mm samples and divided into four study groups. Group 1: Electric brushing with Toothpaste (BTP); Group 2: Electric brushing with Toothpaste+mouthwash (BTP+MW); Group 3: Electric brushing with Toothpaste+whitening pen (BTP+WP); Group 4: Electric brushing with Toothpaste+mouth wash+whitening pen (BTP+MW+WP). Samples were submitted toVickers micro-hardness test and visualized using scanning electron microscopy (SEM). Results. All groups, with the exception of group 1, showed a decrease in micro-hardness values after applying the treatments (p<0.05). Likewise, when comparing the values after the treatments between the groups, significant statistical differences were found in all of comparisons except for those of groups 2 and 4. SEM images showed changes in the morphology in all the study groups with the exception of group 1. Conclusion. Significant changes such as decrease in micro-hardness as well as in the topography of the enamel surface such as elevations, craters, porosities and etching patterns were founded after the use of the combination of auxiliaries of oral hygiene with whitening agents.